The Effect Of Participation On Residents' Satisfaction In Multi Storey Housing Project in The Gaza Strip, Palestine (Abstract) - Ms Aljirrbi, Suheir (2013)
Penyertaan penghuni merupakan pertimbangan penting di kawasan perumahan berbilang tingkat